Handling Cart People, Clowns, Homeless Beggars and Street Children in Banjarmasin City - Junaidy Junaidy*; Rizky Subhan; Dewi Merdayanty; Sitna Hajar Malawat; Sugiannor Sugiannor (Riwayat: Educational Journal of History and Humanities, 2023)
This research aims to find out how the implementation and effectiveness of the program for handling Cart People, Clowns Homeless Beggars and street Children in the City of Banjarmasin. The research method used is a qualitative method as a research procedure that produces descriptive data in the form of words. Research location in Banjarmasin City. The data collection techniques used were observation, interviews and documentation. Test the validity of the data by triangulating data collection techniques. Data analysis techniques using data collection, data reduction, data presentation and drawing conclusions. The results of the research show that the implementation of the program for handling program target objects is not running optimally, the organization of the formation of resource arrangements and infrastructure to support the program is classified as inadequate to reach all program target objects, Program interpretation has been carried out well, in accordance with leadership directions and SOPs and applications/implementations related to routine activities, implementation standards and activity targets and inter-sectoral cooperation has been carried out well. The effectiveness of the program targets consisting of the program target objects (cart people, clowns, flats and anjal) and the community is good. The socialization of the program has not been carried out optimally, the success of the program has been effective, monitoring of the program has been carried out but is not yet optimal.